STRATEGI KOMUNIKASI PEMASARAN TAMAN WISATA ALAM ANGKE KAPUK DALAM MENINGKATKAN KUNJUNGAN - Putri Adinda Trisia; Rizki Nurul Nugraha (Sekolah Tinggi Pariwisata Mataram, 2022)
A marketing communication strategy is a strategy in conveying certain information to consumers about the products offered either directly or indirectly. Marketing communication strategies in a tourism destination have many benefits in their application such as increasing the number of visitors and seeing the effectiveness of promotions in the area, with this research can also find out the effectiveness of the use of marketing communications in the Angke Kapuk Nature Tourism Park area. This research began in July 2022 until it was completed. This research was conducted in the Mangrove Natural Tourism area, North Jakarta. As for the resource persons, namely the key information, namely the employees, managers of the Angke Kapuk Tourism area and visitors to the Angke Kapuk Nature Tourism Park. Data is obtained by the method of interviewing the manager.